Forms of Fighting: A Micro-Social Analysis of Bullying and In-School Violence - Malette, Nicole (Canadian Journal of Education/Revue canadienne de l'éducation, 2017)
Current empirical research on youth bullying rarely asks students to describe their violent encounters. This practice conflates incidents of aggression that may actually have different forms and features. In this article I provide the results of a qualitative analysis of retrospective interviews with high school youth about their experiences of in-school violence. I test for and confirm the occurrence of five types of violence: bullying, scapegoating, peer-to-peer honour contests, group fights, and retaliatory violence. My testing method involves analyzing whether the social dynamics, such as offender–victim social status and the ratio of aggressors to victims, identified in theoretical work, occur empirically. I show that there is variability in the social dynamics that map onto the five types of violence, listed above. In ignoring these differences, violence prevention policy and practice runs the risk of prolonging student conflict.